Early Protein Markers of Necrotizing Enterocolitis in Plasma of Preterm Pigs Exposed to Antibiotics - Jiang, Yan-Nan; Muk, Tik; Stensballe, Allan; Nguyen, Duc Ninh; Sangild, Per Torp; Jiang, Ping-Ping (Frontiers in Immunology, 2020)
Background: Most hospitalised preterm infants receive antibiotics in the first days of life to prevent or treat infections. Short-term, early antibiotic treatment may also prevent the microbiota-dependent gut inflammatory disorder, necrotising enterocolitis (NEC). It remains a challenge to predict NEC and few early blood diagnostic markers exist. Using preterm pigs as model for infants, blood parameters and plasma proteins affected by early progression of NEC were profiled in preterm pigs subjected to oral, systemic or no antibiotics after preterm birth. Methods: Preterm newborn pigs were treated with saline (CON) or antibiotics (ampicillin, gentamicin and metronidazole) given enterally (ENT) or parenterally (PAR), and fed formula for four days to induce variable microbiome-dependent sensitivities to NEC. The gut was collected for macroscopic scoring of NEC lesions and blood for haematology, blood biochemistry and LC/MS-based plasma proteomics. Statistical modelling was applied to detect plasma proteins affected by NEC and/or antibiotics. Results: Analysed across different antibiotic regimens, NEC progression was associated with altered blood parameters and abundance of 89 plasma proteins that were functionally involved in extracellular membrane destruction, lipid metabolism, coagulopathy and acute phase response. Large NEC-related changes were observed in abundance of RBP4, FGA, AHSG, C5, PTPRG and Α-1-antichymotrypsin 2, indicating potential serving as early markers of NEC. Conversely, antibiotic treatment, independent of NEC, affected only four proteins with main differences found between ENT and CON pigs. Conclusion: Early postnatal development of NEC lesions is associated with marked plasma protein changes that may be used for early NEC diagnosis.